Strategi Ekspor Bisnis Minuman Bandrek ‘Sifa’ ke Asia Tenggara - Sitorus, Marthaleina Ruminda; Purwoko, Harry; Fadillah, Ridho Rizky; Kharisma, Alvian Farisqi Dwi; Parlindungan, Purbanuara (Jurnal Pengabdian dan Kewirausahaan, 2024)
CV. Siraj Fawwaz is an MBKM business located in Warungkupa Village, Gununghalu District, Bandung Regency, West Java. The business engaged in traditional bandrek beverage products is known as Sifa. This service activity generally aims to describe the description of Sifa's bandrek beverage business model. Service activities are carried out by discussing and describing problems in the beverage industry. Through structured interviews, this service activity is executed by describing the business model canvas and SWOT analysis. The interview was conducted to find out the marketing strategy of Sifa's bandrek beverage business. The results of this activity show that this bandrek beverage product has used the business model canvas method to determine marketing strategies with nine elements of the business model canvas block. The results of the SWOT analysis show that the bandrek beverage business is in quadrant I which is a profitable position. This beverage business has the opportunity and strength to distribute products to highland areas, increase the number of product variants and increase good cooperation with suppliers. Thus, community efforts in the sub-district area can be developed and improved. This bandrek beverage business has the opportunity to develop and increase the production of healthy local drinks. This bandrek beverage business can increase the market by utilizing information technology and social media. Market reach can be developed so that this bandrek beverage business can export its products to Southeast Asia.